Infância negra e mídias digitais: uma análise de canais do YouTube realizados por meninas negras - Santos, Jussara Nascimento do (2018)
The present research was conducted between January and August, 2018 with the principal reason to analyse four channels on Youtube from black girls between seven and eleven years old. The aim was identifying in those channels the presence of theme relating to the issue of race in the published videos. Assuming they have expressed  themselves, showing racism experience which contributes to the spectator thinking about it. The investigation has started with systematic follow-up during 8 months by Ellis Mc. channel on Youtube channels from: Ana Clara Barbosa (11 years old), Carolina Monteiro (11 years old), Emily Lima (8 years five months old). Utilising the ethnographic by silence observation, when the channel was observed without any intervention from the researcher in comments or ‘likes’. The posts published and videos with focuses on topics debated were analysed weekly. In conclusion, the four channels are at least inserted in logical cultural industry, when the culture becomes product. According to the questions about racism: Carolina Monteiro and Ellis Mc have brought critical debates showing a valid repertoire of black race for their audience. However, Ana Clara Barbosa e Emily Lima doesn’t make any mention about race, instead they reproduce the same as the other channels.     The study focused mainly on formation, cultural industry, individual and societal, and ideological theories found within Critical and Societal Theory. (Reference)